Dhuafa empowerment through oxytocin massage in the PCM area of East Pontianak - Widyastutik, Otik; Putri, Zulfa Aliska (Universitas Muhammadiyah Magelang, 2021)
Data on the achievement of normal nutritional status in children aged 0-59 months in East Pontianak (67.7%) as well as short and very short nutritional status (32.3%). Interestingly, one of the determinants of the nutritional status of children under five, namely the coverage of exclusive breastfeeding is still very low (25%). Through this program, poor community groups (dhuafa), Muhammadiyah members, were empowered to have knowledge and skills that focus on educational efforts about lactation management using the oxytocin massage technique. Oxytocin massage is one of the stages in lactation management which aims to facilitate breast milk. The East Pontianak PCM Tabligh Council is one of the potential platforms in developing this program. Activities started from providing education, training in oxytocin massage and mentoring. Based on the results of the evaluation, it is known that there was an increase in knowledge about oxytocin massage. By the end of this activity, it was hoped that the participants will be able to become a cadre group of PCM East Pontianak capable of massaging oxytocin, as well as promoters of breastfeeding care activities.